Performance Management System at a Malaysian Higher Education Institution: a case study - Abdullah, Nur Anisah (2010)
This case study illustrates the design of a new performance measurement and management system for a Malaysian international higher learning institution (HLI). The case describes the processes involved in the design and implementation of a central system and the cascading to all kulliyyahs , centres, divisions, and institutes. It explores the reasons for the new system, and looks at the design of a system of control tailored to the needs of the institution. The observations give an understanding about the challenges faced by a higher learning institution and its plight in search of a tool that facilitates decision-making and the management of strategy. Evidence reiterates similar concerns raised in various reports on how the effectiveness of performance measurement system depended on several elements, which include the need to (i) ensure buy-in through participation from various levels of staff during design phase, where this buy-in helped roll-out implementation more effectively; (ii) alignment of measures to organisational objectives to assure relevance; (iii) an integrated central database to ameliorate the labour intensiveness of data collection; and (iv) realise the investments of time and resources required for a performance measurement system to progress through phases of development and maturity before any sense making. The case reports a positive and beneficial experience for senior officials where their engagement in the development phases supported an improved understanding of the direction of the institution; and that the implementation of the new system provided them with a platform to review and discuss performance or non-performance, a process which informed and facilitated the management of strategy.